Kesejahteraan Spiritual dan Dampaknya terhadap Kecemasan, Depresi, dan Kualitas Hidup Pasien Hemodialisa: Sebuah Tinjauan Literatur - Rabuzain Rabuzain; Wantonoro Wantonoro; Asykuri Asykuri (Jurnal Keperawatan Florence Nightingale, 2026)
Patients with chronic kidney disease undergoing hemodialysis frequently experience various psychological problems, including anxiety, depression, and decreased quality of life. In recent years, spiritual well-being has received increasing attention as a potential factor that may help patients adapt to the burden of chronic illness. This study aimed to review and synthesize scientific evidence regarding the relationship between spiritual well-being, anxiety, depression, and quality of life among hemodialysis patients. This study employed a Literature Review approach following the PRISMA guidelines. Articles published between 2020 and 2025 were retrieved from PubMed, Scopus, ScienceDirect, and Google Scholar databases. The selected studies were screened based on predetermined inclusion and exclusion criteria. A total of ten quantitative studies met the eligibility criteria and were included in the review. The findings indicated that spiritual well-being was consistently associated with better psychological outcomes among hemodialysis patients. Higher levels of spirituality were linked to lower levels of anxiety and depression, improved quality of life, and more adaptive coping abilities. In addition, several studies reported that spirituality contributed to better treatment adherence and greater life satisfaction. However, variations in findings were observed due to differences in cultural contexts, participant characteristics, and measurement instruments. In conclusion, spiritual well-being is an important factor associated with the mental health and quality of life of hemodialysis patients. The integration of spiritual aspects into nursing care may support a more holistic approach to patient management. Further studies with more rigorous research designs are needed to clarify the underlying mechanisms of this relationship.